2012
DOI: 10.1051/0004-6361/201118091
|View full text |Cite
|
Sign up to set email alerts
|

The Type II supernovae 2006V and 2006au: two SN 1987A-like events

Abstract: Context. Supernova 1987A revealed that a blue supergiant (BSG) star can end its life as a core-collapse supernova (SN). SN 1987A and other similar objects exhibit properties that distinguish them from ordinary Type II Plateau (IIP) SNe, whose progenitors are believed to be red supergiants (RSGs). Similarities among 1987A-like events include a long rise to maximum, early luminosity fainter than that of normal Type IIP SNe, and radioactivity acting as the primary source powering the light curves.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(97 citation statements)
references
References 48 publications
5
89
1
1
Order By: Relevance
“…The r-band light curve shows a rise of ∼0.8 mag in the first 10 d. Then it settles onto an early plateau between days 10 and 30, and it finally starts a long rise to peak (∼0.9 mag brighter than the plateau) that occurs at ∼75 d. All of the other bands reach maximum around the same time, and between days 10 and 30 they also exhibit an early-time plateau, preceded by a decline in the case of B and g. Since the followup observations started 2 weeks later for these filters than in the r band, no early-time rise could be detected. The overplotted and scaled light curves of SN 2006au (from Taddia et al 2012) clearly show the close resemblance of PTF09gpn to this SN 1987A-like SN.…”
Section: Supernova Light Curves and Colorsmentioning
confidence: 75%
“…The r-band light curve shows a rise of ∼0.8 mag in the first 10 d. Then it settles onto an early plateau between days 10 and 30, and it finally starts a long rise to peak (∼0.9 mag brighter than the plateau) that occurs at ∼75 d. All of the other bands reach maximum around the same time, and between days 10 and 30 they also exhibit an early-time plateau, preceded by a decline in the case of B and g. Since the followup observations started 2 weeks later for these filters than in the r band, no early-time rise could be detected. The overplotted and scaled light curves of SN 2006au (from Taddia et al 2012) clearly show the close resemblance of PTF09gpn to this SN 1987A-like SN.…”
Section: Supernova Light Curves and Colorsmentioning
confidence: 75%
“…However, since we know from modeling (e.g. Utrobin & Chugai 2011;Taddia et al 2012) that most of our BSG SNe arise from stars that are more massive (M ZAMS ∼ 20 M ) than the typical RSG progenitors of SNe IIP (∼10 M ), it seems that this mass difference is too small to be detected by the NCR method (see also discussion in Crowther 2013). The weak association with H ii regions for the massive progenitors of 1987A-like SNe could also be interpreted in terms of binary scenarios giving rise to longer lifetimes.…”
Section: Discussionmentioning
confidence: 97%
“…Before these events, SN 1998A (Pastorello et al 2005) had been suggested to result from the explosion of a BSG star. Recently we published an analysis of two additional SN 1987A-like transients (SNe 2006V and2006au;Taddia et al 2012). Through the modeling of the bolometric light curves, we determine progenitor radii to less than 100 R .…”
Section: Introductionmentioning
confidence: 99%
“…After a thorough search for SNe in other public targets, a sample of 6 galaxies that hosted 11 SNe (4 Ia, 7 II) have been compiled. Besides 7 typical SN II and Ia, the following four SNe had more precise classifications: SN 2000ft was discovered in NGC 7469 by using radio observations and showed similar evolution properties than other compact radio sources identified as SN II (Alberdi et al 2006); SN 2000cb showed similar photometric behaviour than SN 1987A, which are thought to be SN II resulting from the explosion of blue supergiants (Pastorello et al 2005;Taddia et al 2012); SN 1993R was typed as a peculiar SN similar to the subluminous SN Ia class 1991bg-like, but with stronger Ca II NIR triplet (Filippenko & Matheson 1993). Finally, SN 2005ip spectra showed that it was interacting with the surrounding circumstellar medium and it was typed as SN IIn (Stritzinger et al 2012).The programs that proposed the observations of these 5 galaxies, observation periods, exposure times, and seeing at the time of observations are summarized in Table 1. MUSE delivers an impressive set of ∼100,000 spectra per pointing covering most of the optical domain.…”
Section: Observationsmentioning
confidence: 99%